THE PREDICTABLE TIME SCALE OF LANDSLIDES - Qin S.Q.; Jiao J.J.; Wang S.J. (My University, 2001)
Recent nonlinear dynamical systems (NDS) techniques have been developed to analyse chaotic time series data. According to NDS theory, the correlation dimension and predictable time scale are evaluated from a single observed time series. Two case studies are presented to demonstrate that chaos exists in the evolution of a landslide and the predictable time scale must be considered. The possibility for long-term, medium-term and critical prediction is discussed.
Keywords: CHAOS; PREDICTABLE TIME SCALE -LANDSLIDE; LYAPUNOV EXPONENT